Conflitos Socioambientais, Educação Ambiental e Participação Social na Gestão Ambiental - Hiroo Saito, Carlos; Ruscheinsky, Aloísio; da Purificação de Bastos, Fabio; Bandeira Almeida Nunes, Jacy; Fernandes Silva, Luciano; Carvalho, Luiz Marcelo de (Sustainability in Debate, 2011)
This is synthesis of the debates held during the round-table “Socioenvironmental conflicts, environmental education and social participation on environmental management”, at the V ENANPPAS (2010), which has focused on the discussion of four main themes: Socioenvironmental conflicts and the myths of social participation; Socioenvironmental conflicts and the uncertainty of conditions to environmental education immersed in problems and conflicts; Solution of Socioenvironmental conflitcts ”“ actions mediated by instrumental rationality and emancipatory interest; Positive actions as dialogical-problematizing practice on concrete reality. From an initial provocative text, each member has brought his first contribution, followed by new questions as consequence of these speeches. The hole debate was recorded, transcripted and made a synthesis to present in this manuscript form.